Ù ÙÙØ¬ Ø§ÙÙÙØ§Ø³ ÙÙ ÙÙÙ Ù Ø®ØªÙÙ Ø§ÙØØ¯ÙØ« Ø¹ÙØ¯ Ø§Ø¨Ù ÙØªÙØ¨Ø© Ø§ÙØ¯ÙÙÙØ±Ù - ghozali, abdul malik (Center for Research and Development of Religious Literature and Heritage, 2016)
AbstractProphet Tradition (hadith) is the second main source in Islam. Unlike Koran that has completely validated as revelation, meanwhile hadith must be examined its validation of trasmission and matan. Therefore, problematic hadithÂ appeared, in transmission or matan. Especially, the problematic hadith in wich its matan contradicted, that called âmusykil al-haditsâ or âmukhtalaf al-haditsâ. Mukhtalaf al-Hadith, appearly, its matan contradicted with Koran, other equal hadith, axioma or reality. So, Mukhtalaf al-HaditsÂ is more debatable. Muâtazila who representative of Rasionalits, rejected existence of mukhtalaf al-hadits as source of religion. Otherwise, Tradisionist (Ahl HadÄ«ts) accepted it as source of religion, when its transmission comfirmed/validated. To realease contradiction of mukhtalaf hadits matan, Ibnu Qutayba, one of Muhaddits used Â many rational methods; analogy (qiyÄs ushÅ«lÄ«) and syllogism (qiyÄs manthiqÄ«). This research used content analysis with some approaches; Jurisprudence, Logic, Ushul Fiqh.